1991
DOI: 10.1177/089124391005002005
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Publishing in Sociology

Abstract: As in other fields, scholarly publication in sociology is not only the key to career success but also the route by which feminist analyses and perspectives become known to others in the discipline. A growing literature has analyzed women's and men's rates of publication, but the gender politics of the prepublication production of research and gender differences in reputation building after publication remain underexplored. This report reviews the current state of knowledge about sociological publishing at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
1
6

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 36 publications
4
70
1
6
Order By: Relevance
“…Women's inroads into professional sociology are apparent in their increased representation as authors (Grant and Ward 1991;Roos and Jones 1993). The proportion of all articles (n=1,274) with females as first or sole-authors remained both low (around 10%) and relatively stable until 1985, after which there was a steady and marked increase in the proportion of articles with a woman serving as the sole or first author (up to 32% in the early 2000s).…”
Section: Gendered Patternsmentioning
confidence: 97%
“…Women's inroads into professional sociology are apparent in their increased representation as authors (Grant and Ward 1991;Roos and Jones 1993). The proportion of all articles (n=1,274) with females as first or sole-authors remained both low (around 10%) and relatively stable until 1985, after which there was a steady and marked increase in the proportion of articles with a woman serving as the sole or first author (up to 32% in the early 2000s).…”
Section: Gendered Patternsmentioning
confidence: 97%
“…In more recent eras, women also have been more likely to focus their scholarship on women and other disadvantaged groups (Ward and Grant 1991), and a concern for linking activism and scholarship is important in the lives of sociologists who identify as feminist, especially in younger professional generations. For example, Sociologists for Women in Society, the organization that sponsors the journal Gender & Society, at its midyear meetings has focused much of the program on links between scholarship and activism.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is variation in the type of sociological scholarship produced by women, scholars have suggested that women show significant differences from men in the theoretical approaches they employ (Cancian 1992;Kramarae and Spender 1992;Nielsen 1991;Stacey and Thorne 1985;Ward and Grant 1991b), the ways in which they organize research teams and other intellectual collaborations (Ward and Grant 1991a), the topics they select (Roby 1992;Ward and Grant 1985), the methods they employ (Reinharz 1992a(Reinharz , 1992b, the types of evidence they bring to bear on sociological inquiry (Fonow and Cook 1991;Grant, Ward, and Rong 1987;Grant and Ward 1991;Reinharz 1992aReinharz , 1992b, and their perspectives on the links between research and praxis (Cancian 1992;Platt 1983;Reinharz 1992aReinharz , 1992bRoberts 1981;Stanley 1992Stanley , 1990Stanley and Wise 1983). Women sociologists are more likely than men to critique traditional "mainstream" social theories, to value experiential knowledge, to write data-based rather than theoretical or conceptual articles, to challenge the perspective that objectivity is possible or desirable, to work in collaborative, nonhierarchical research teams that sometimes include those who are the focus of the research, to concentrate on gender as a topic for serious sociological inquiry (and to critique the exclusion of gender in much sociological research), to use qualitative, interpretive methods more often than men do, and to advocate links between research and praxis, especially applications of research that benefit women and other disadvantaged groups.…”
Section: Women and Sociological Researchmentioning
confidence: 97%
“…Most studies of journals use random samples (McNamee, Willis, and Rotcheford, 1990) or focus on periods (Crase 1992;Grant and Ward, 1991;Mehdizadeh, 1993). Given the short publication history (10 years) and number of volumes (n=10) of TGPS relative to more established specialty, state, regional, national, and international sociology journals, our study captures the total population of articles, early in the journal's tenure.…”
Section: The Great Plains Sociologistmentioning
confidence: 99%